The study of renin-angiotensin-aldosterone in experimental diabetes mellitus - Üstündag, B; Cay, M; Naziroglu, M; Dilsiz, N; Crabbe, MJC; Ilhan, N (Wiley, 1999)
It is generally accepted that hypertension and other vascular pathologies increase in diabetes mellitus (DM) patients as a result of the renin-angiotensin-aldosterone (RAA) system. In this study, changes in the renin-angiotensin-aldosterone (RAA) system level was determined in Streptozotocin (STZ)-injected rats. A total of 46 female Wistar albino rats (180-220 g body weight) was utilized in these experiments. STZ was given intraperitoneally to induce diabetes in rats. Streptozotocin (60 mg kg(-1) body weight) was dissolved in 0.1 M citrate-phosphate buffer (pH 4-5). The non-diabetic rats were injected with sterilized buffer alone to act as a control group. Blood glucose levels were 398 +/- 8.2 mg dl(-1), 488 +/- 11.75 mg dl(-1) and 658 +/- 29.6 mg dl(-1) at days 3, 12 and 30 respectively. The level of plasma renin activity (PRA) was measured as 7.69 +/- 1.07 ng ml(-1) h(-1); 1.82 +/- 0.22 ng ml(-1) h(-1) and 0.67 +/- 0.12 ng ml(-1) h(-1) at days 3, 12 and 30, respectively. These values showed that the PRA levels are decreased with increased time period. Serum angiotensin converting enzyme (ACE, E.C. 3.4.15.1) levels were increased at days 12 and 30 (p < 0.05 and p < 0.005), whereas serum aldosterone levels were increased at days 3 and 12 (p < 0.05). The level of urea and creatinine increased at days 12 and 30 (p < 0.05 and p < 0.005, respectively) when compared to the control group. The data from these experiments indicate that the PRA level decreased whereas ACE activity level increased in diabetic rats compared with the control. Aldosterone levels increased at the first stage of the experiment, but then decreased by the end of the experiment as a result of changes in renin and ACE levels. Copyright (C) 1999 John Wiley & Sons, Ltd.
Keywords: angiotensin converting enzyme (ACE); streptozotocin (STZ); diabetes mellitus (DM)